2020
DOI: 10.1002/jcu.22922
|View full text |Cite
|
Sign up to set email alerts
|

A new prenatal sonographic sign of epidermolysis bullosa

Abstract: We report on the prenatal sonographic appearance of epidermolysis bullosa (EB). The third viable pregnancy of a consanguineous couple was found at 23 weeks to have dysplastic external ears and nose. The neonate was born at 33 weeks and was found to have junctional EB with pyloric atresia. On reviewing the 23-week ultrasound images, skin denudation was evident. This is a report of visualization of skin denudation in EB. When EB is suspected prenatally, special attention should be given to the visualization of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been reported that fetal stomach growth should be evaluated according to gestational age and normal fetal stomach at 31-33 weeks of gestation is 2.8 ± 0.9 cm in size (Goldstein et al, 1987). In EB-PA, echogenic amniotic fluid (snowflake sign), dysplasia of external ear and nose, and complete chorioamniotic separation can also be seen without skin blistering (Chen et al, 2021). Usui et al reported that 92% of familial cases had polyhydramnios (Usui et al, 2013) (Okoye et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fetal stomach growth should be evaluated according to gestational age and normal fetal stomach at 31-33 weeks of gestation is 2.8 ± 0.9 cm in size (Goldstein et al, 1987). In EB-PA, echogenic amniotic fluid (snowflake sign), dysplasia of external ear and nose, and complete chorioamniotic separation can also be seen without skin blistering (Chen et al, 2021). Usui et al reported that 92% of familial cases had polyhydramnios (Usui et al, 2013) (Okoye et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…EB was first hypothesized [23] on prenatal ultrasounds in a couple at risk due to the presence in the amniotic fluid of "snowflakes" (namely echogenic particles). Other related sonographic findings reported in the literature include enlarged stomach and polyhydramnios [24,25] (due to frequent association with pyloric atresia), deformed external ears and contracted fisted hand [24], shortening of long bones [26], complete chorioamniotic membrane separation [27] and localized skin denudation [28]. However, all these references are sporadic and lack scientific solidity, so a definite prenatal ultrasound diagnosis of EB still remains a fundamentally unresolved challenge.…”
Section: Maternal-fetal Clinical Monitoringmentioning
confidence: 99%